One Word That Will Change Your Life, Expanded Edition - Britton, Dan (Wiley, 2013)
The guide to creating simplicity in your world and developing a discipline for life, now in a full-color, expanded edition One Word explains how to simplify your life and business by focusing on just ONE WORD for the entire year. The simplicity of choosing one word makes it a catalyst for life-change. Clutter and complexity lead to procrastination and paralysis, while simplicity and focus lead to success and clarity. By celebrated authors Dan Britton, Jimmy Page, and Jon Gordon, One Word That Will Change Your Life shows you how to cut through to the core of your intention for t.
Includes bibliographical references and index. - Print version record
Keywords: Self-actualization (Psychology) -- Religious aspects -- Christianity; Self-actualization (Psychology); Motivation (Psychology) -- Religious aspects -- Christianity; Motivation (Psychology); Christian life; Commitment (Psychology); Motivation; Motivation (Psychologie); Aspect religieux; Christianisme; Motivation (Psychologie); Vie chrétienne; Engagement; Motivation (Psychology); Religious aspects; Christianity; Self-actualization (Psychology); Religious aspects; Christianity